A new route to N-aromatic heterocycles from the hydrogenation of diesters in the presence of anilines. Issue 10 (17th August 2017) - Shi, Yiping; Kamer, Paul C. J.; Cole-Hamilton, David J.; Harvie, Michelle; Baxter, Emma F.; Lim, Kate J. C.; Pogorzelec, Peter
Abstract : The hydrogenation of dicarboxylic acids and their esters in the presence of anilines provides a new synthesis of heterocycles. Abstract : The hydrogenation of dicarboxylic acids and their esters in the presence of anilines provides a new synthesis of heterocycles. [Ru(acac)3 ] and 1, 1, 1-tris(diphenylphosphinomethyl)ethane (triphos) gave good to excellent yields of the cyclic amines at 220 °C. When aqueous ammonia was used with dimethyl 1, 6-hexadienoic acid, ε-caprolactam was obtained in good yield. A side reaction involving alkylation of the amine by methanol was suppressed by using diesters derived from longer chain and branched alcohols. Hydrogenation of optically pure diesters (dimethyl ( R )-2-methylbutanedioate and dimethyl ( S )-2-methylbutanedioate) with aniline afforded racemic 3-methyl-1-phenylpyrrolidine in 78% yield.